Fifty playwrights on their craft - Jester, Caroline; Jester, Caroline; Svich, Caridad (Bloomsbury Methuen Drama, an imprint of Bloomsbury Publishing Plc, 2018)
In a series of interviews with fifty playwrights from the US and UK, this book offers a fascinating study of the voices, thoughts, and opinions of today's most important dramatists. Filled with probing questions, Fifty Playwrights on their Craft explores ideas such as how does playwriting help a global dialogue; where do dramatists find the ideas that become the stories and narratives within their plays; how can the stage inform the writer's creative process; how does crossing boundaries between art forms push the living art form of theatre-making forward; and will there be playwrights in another 50 years? Through these interrogating interviews we come to understand how and why playwrights write what they do and gain insight into their processes and motivations. Together, the interviews provide an inter-generational dialogue between dramatists whose work spans over six decades. Featuring interviews with playwrights such as Edward Bond, Katori Hall, Chris Goode, David Greig, Willy Russell, David Henry Hwang, Alecky Blythe, Anne Washburn and Simon Stephens, Jester and Svich offer an unprecedented view into the multiple perspectives and approaches of key playwrights on both sides of the Atlantic.